2017
DOI: 10.1136/oemed-2016-104080
|View full text |Cite
|
Sign up to set email alerts
|

Interactions between occupational exposure to extremely low frequency magnetic fields and chemicals for brain tumour risk in the INTEROCC study

Abstract: There was no clear evidence for interactions between occupational ELF and chemical exposures in relation to glioma or meningioma risk observed. Further research with more refined estimates of occupational exposures is recommended.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 39 publications
0
7
0
Order By: Relevance
“…Due in part to the widespread exposure of the general population to magnetic fields (MF) emitted by systems related to the generation, distribution and use of electricity, a debate has been going on for years focusing on the possibility that exposure to power frequency (50-60 Hz) fields could have adverse health effects, being those related to cancer development and/or promotion the most widely studied ones. Although the evidence of an association between chronic occupational exposure to these extremely low frequency (ELF) MF and the incidence of cancer is limited [1][2][3], the International Agency for Research on Cancer (IARC) of the World Health Organization, included this type of physical agent in its list of possible carcinogens, class 2B (IARC 2002 [4]), mainly on the basis of the epidemiological link between incidence of childhood leukaemia and residential exposure to MF [5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…Due in part to the widespread exposure of the general population to magnetic fields (MF) emitted by systems related to the generation, distribution and use of electricity, a debate has been going on for years focusing on the possibility that exposure to power frequency (50-60 Hz) fields could have adverse health effects, being those related to cancer development and/or promotion the most widely studied ones. Although the evidence of an association between chronic occupational exposure to these extremely low frequency (ELF) MF and the incidence of cancer is limited [1][2][3], the International Agency for Research on Cancer (IARC) of the World Health Organization, included this type of physical agent in its list of possible carcinogens, class 2B (IARC 2002 [4]), mainly on the basis of the epidemiological link between incidence of childhood leukaemia and residential exposure to MF [5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…A recent Canadian study found no evidence of an association between PM 2.5 or NO 2 and malignant brain tumors [ 23 ]. Turner et al [ 30 ] reported on malignant tumors of the brain, adjusted for a comprehensive array of personal and area-level confounders, and found no significant association with PM 2.5 , NO 2 or O 3 . When accounting for the different unit scales, the HRs in that study were very similar to those observed in our study.…”
Section: Discussionmentioning
confidence: 99%
“…An ecological study from the US found volatile organic compounds to be associated with county-level incidence of tumors of the CNS [29]. Two studies of a cohort from the US found no association between a range of air pollutants (particulate matter with a diameter less than 2.5 μm (PM2.5) and 10 μm (PM 10 ), sulphur dioxide, nitrogen dioxide, carbon monoxide or ozone (O 3 )) and mortality from malignant tumors of the brain [30,31]. In an exploratory analysis of 54,304 members of the Danish Diet Cancer and Health cohort, mean outdoor residential NO x levels since 1971 were associated with an incidence rate ratio of 2.28 (95% confidence interval (CI): 1.25-4.19, cases = 95) per 100 μg/m 3 increase, for tumors of the brain and central nervous system [26].…”
Section: Introductionmentioning
confidence: 99%
“…The field of bioelectromagnetic research is still mainly focused on the initial exploration of biological effects. Accordingly, many countries are continuously studying the possible biological effects of various EMF sources and effective protection measures in addition to the application of EMF [4][5][6].…”
Section: Introductionmentioning
confidence: 99%